Meteorology today : - Ahrens, C. Donald (Thomson/Brooks/Cole, 2003)
Meteorology today has for many years been one of the most widely used and authoritative texts for the introductory meteorology course. Each edition is extensively reviewed by leading researchers in the field to ensure that the text remains completely up-to-date and reflects today's current understanding of meteorological concepts. Author Donald Ahrens has been widely praised for his ability to explain relatively complicated ideas so that even under-prepared students can understand them. The text's clear and inviting presentation is supplemented by numerous pedagogical features that help augment students' understanding. Introductory stories found at the beginning of each chapter draws students naturally into the discussion. In-chapter reviews then help students to consolidate their understanding as they read, while four types of end-of-chapter exercises provide opportunities for everything from further review to in-class discussion questions. Graphics are carefully designed and subsequently refined so that the key ideas clearly emerge. Many of the photos in the book are taken by the author and provide unmatched images of dramatic weather phenomena. A unique and popular feature over this title's seven editions has been the foldout cloud chart at the back of the book. A wealth of online resources accompanies Meteorology today, Seventh Edition, allowing professors to integrate striking and illuminative interactive weather exercises into their course. Many of the exercises on the Blue skies CD-ROM packaged free with each new copy of the text are tied to downloadable real-time weather data, offering instructors an easy way to bring the exploration of current weather events into the course discussion.